Digital Tax Administration Systems and Taxpayer Compliance: A Qualitative Literature Review - Zahwa Noveliza Nur Safitri; Dea Amirotul Ahlam; Yuni Sukandani; Yohanes Billarminus Mau; Afif Haniatus Sa'diyah (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2026)
This study aims to investigate the impact of digital tax administration systems on taxpayer compliance using a qualitative literature review method. The rapid development of information technology has driven the digital transformation of tax administration, such as e-filing and integrated systems. However, previous studies have reported inconsistent findings regarding their impact on taxpayer compliance. This study employs a descriptive qualitative method using content analysis of 10 relevant research articles published between 2021–2026. The reviewed literature generally suggests that digital tax systems are associated with improved taxpayer compliance, although the findings vary depending on context, research focus, and local institutional factors. These include system usability and reliability, taxpayer knowledge and readiness, as well as service quality and trust in tax authorities. The findings suggest that improving taxpayer compliance requires a comprehensive approach that integrates user-friendly systems, digital literacy, and institutional support.